Using Superior Variety and Application of CI200 to Support Food Security in South Sumatra Swamp Land - Waluyo; Suprihatin Agus; Suparwoto; Jumakir (BIO Web of Conferences, 2023)
Swamp paddy fields with their various problems have enormous potential to support the achievement of national food security. Using superior varieties and determining the exact planting season in the swamp rice cultivation is expected to increase rice productivity and farmers’ income per unit area. The research aims to increase rice production and assess the feasibility of CI200 in swamps. The study used an oversite design with 5 replications in a farmer’s swamp land with an area of 1 ha, in the Gelebek Dalam village, Rambutan District, Banyuasin Regency, South Sumatra Province. Factors tested: 1) superior varieties, there are 4 varieties namely Inpari 32, Inpara 2, Mekongga, and Ciherang, 2) seasons, application of CI200 so that planting is carried out throughout the year, namely the DS (April-August 2021) and RS (October 2021-February 2022). Inpari 32 has the highest productivity compared to other varieties, reaching 6.98 t HDG ha-1. The value of the B/C ratio reached 1.51-2.44 in DS and 1.09-1.98 in RS. Therefore, the application of the CI200 cropping pattern by using NSV which has been adapted can be widely developed to support food security in swamps land.